2014
DOI: 10.1016/j.ymeth.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Humanized FcRn mouse models for evaluating pharmacokinetics of human IgG antibodies

Abstract: A key element for the successful development of novel therapeutic antibodies is to fully understand their pharmacokinetic and pharmacodynamic behavior before performing clinical trials. While many in vitro modeling approaches exist, these simply cannot substitute for data obtained from appropriate animal models. It was established quite early that the unusual long serum half-life of immunoglobulin G’s (IgGs) and Fc domains are due to their rescue and recycling by the neonatal Fc receptor (FcRn). The diverse ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 42 publications
1
66
0
Order By: Relevance
“…It has been determined that the FcRn is responsible for the active transport of molecules containing an Fc domain across the blood retinal barrier and it therefore increases the overall bioavailability. This makes the FcRn clinically relevant not only for the intra-ocular pharmacokinetics of therapeutic monoclonal antibodies, but also for the offtarget effect on VEGF in the periphery by actively transporting the anti-VEGF agents from the vitreous into the systemic circulation (Roopenian & Akilesh 2007;Powner et al 2014;Proetzel & Roopenian 2014). Upon reaching the blood stream, the duration of the anti-VEGF effect is contingent on its systemic half-life.…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that the FcRn is responsible for the active transport of molecules containing an Fc domain across the blood retinal barrier and it therefore increases the overall bioavailability. This makes the FcRn clinically relevant not only for the intra-ocular pharmacokinetics of therapeutic monoclonal antibodies, but also for the offtarget effect on VEGF in the periphery by actively transporting the anti-VEGF agents from the vitreous into the systemic circulation (Roopenian & Akilesh 2007;Powner et al 2014;Proetzel & Roopenian 2014). Upon reaching the blood stream, the duration of the anti-VEGF effect is contingent on its systemic half-life.…”
Section: Discussionmentioning
confidence: 99%
“…These FcRn-humanized mice, unlike wild-type mice, have been shown to be a reliable surrogate for studying human IgG serum half-life. 23,53 Despite reduced circulating murine IgGs, these humanized mice reliably predicted antibody half-lives in primates when challenged with clinical mAbs for which PK data were available. 54 Moreover, whereas human IgG binding and pH dependency are highly similar for human and monkey FcRn, human and murine FcRn have significant molecular differences rendering wild-type mice an inadequate model for studying half-life of engineered human IgGs.…”
Section: Discussionmentioning
confidence: 99%
“…15 The results showed no detectable differences in half-lives between Tg32 and Tg32/hb 2 m mice, indicating functional human-mouse hybrid FcRn complexes were formed in the Tg32 transgenic mice systems. 15 PK studies in Tg32 hemizygous mice also showed high correlation of antibody clearance to human (Pearson r D 0.99, p< 0.001), suggesting that Tg32 could serve as an animal model for translational PK of Fc-containing biotherapeutics. 16 Therefore, establishing a quantitative hFcRn protein tissue expression profile in Tg32 will provide a key parameter for translational PBPK models for human PK predictions.…”
mentioning
confidence: 89%